Radioluminescence, thermoluminescence and dosimetric properties of ZnO ceramics - Grigorjeva, Larisa; Zolotarjovs, Aleksejs; Sokovnin, Sergei Y.; Millers, Donats K.; Smits, Krisjanis; Il'ves, Vladislav G. (Elsevier Ltd, 2017)
Two types of ZnO ceramics were fabricated and characterized by XRD, SEM methods. The radioluminescence spectra were measured within the 300–550 K range. The defect luminescence band peaking at ~2.35 eV is the dominant one in radioluminescence spectra in both of the fabricated ceramics. The thermostimulated luminescence (TSL) glow-curves were measured after X-ray irradiation at 300 K. It was concluded that the complex overlapping peak within the 320–450 K temperature range consists of two components (~360–375 K and 400–420 K). The ratio of component intensities differs in both ceramics. The positions of high temperature TSL components (480–520 K) also differ in both samples; therefore not only sintering conditions but also the properties of the initial powder are very important for characteristics of TSL. A linear dependence of peak intensity on irradiation dose was observed up to ~3 kGy for ceramic 1 and up to 9 kGy for ceramic 2.
The authors gratefully acknowledge the financial support for this work from research grant ERA.NET RUS Plus Nr.609556 and from the SFERA II project Transnational Access activities (EU 7th Framework Programme Grant Agreement no 312643) for supporting ZnO nanopowders preparation.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; ZnO ceramic; Sintering; Thermostimulated luminescence; Dosimetry